Embedding patient and public involvement: Managing tacit and explicit expectations - Fiona Poland; Georgina Charlesworth; Phuong Leung; Linda Birt (Health Expectations, 2019)
Abstract Background Evidencing well‐planned and implemented patient and public involvement (PPI) in a research project is increasingly required in funding bids and dissemination activities. There is a tacit expectation that involving people with experience of the condition under study will improve the integrity and quality of the research. This expectation remains largely unproblematized and unchallenged. Objective To critically evaluate the implementation of PPI activity, including co‐research in a programme of research exploring ways to enhance the independence of people with dementia. Design Using critical cases, we make visible and explicate theoretical and moral challenges of PPI. Results Case 1 explores the challenges of undertaking multiple PPI roles in the same study making explicit different responsibilities of being a co‐applicant, PPI advisory member and a co‐researcher. Case 2 explores tensions which arose when working with carer co‐researchers during data collection; here the co‐researcher's wish to offer support and advice to research participants, a moral imperative, was in conflict with assumptions about the role of the objective interviewer. Case 3 defines and examines co‐research data coding and interpretation activities undertaken with people with dementia, reporting the theoretical outputs of the activity and questioning whether this was co‐researcher analysis or PPI validation. Conclusion Patient and public involvement activity can empower individual PPI volunteers and improve relevance and quality of research but it is a complex activity which is socially constructed in flexible ways with variable outcomes. It cannot be assumed to be simple or universal panacea for increasing the relevance and accessibility of research to the public.